Vivi Citra Yuselvia (NIM: 09030156), Persepsi Masyarakat dalam Memelihara Hutan Lindung di Kanagarian Paru Kecamatan Sijunjung Kabupaten Sijunjung - Yuselvia, Vivi Citra; Dasrizal, Dasrizal; Farida, Farida (Pendidikan Geografi, 2014)
ABSTRACTS            Maintenance of protected areas needs to be done in accordance with the comprehension, awareness and community action preserve in the forest. So that community know the importance of program reforestation which under began to decrease. The aim of this study was to get the data or information and analyze in depth perception protected the community forest preserve in Paru district Sijunjung subdistrict Sijunjung regency.Type of research is qualitative, information taken with technique purposive sampling, with the research subject or respondent were communities in Paru district Sijunjung subdistrict Sijunjung regency. A data collected is about society perception the protected forest preserve in terms of understanding, pay attention, and action.The results of study indicate that public perception the society understanding in maintaining good protected relatively forest. That all society almost know the step how to keep the forest in order to good remain and the society are participated in term of reforestation protected forest. While they have care in maintaining forest that are still classified as moderate or sufficient, that all still society which commit abuses cutting against forest without replanting and just people use the seeds given forest service only. Community action in the forest preserve have been good quite. This can be seen from society awareness to take action against those violate the protected forest region and reported to au teohrities for the sake of success together. Maintenance of protected forest is further enhanced in the future to redure the forot destruction.